Pengaruh Prakyik Kerja Lapangan Sertifikasi Kompetensi dan Soft Skill terhadap Kesiapan Kerja Siswa SMK Dimoderasi Oleh Minat Kerja - Heribertus Wibigunawan; Juan Barus Gultom (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Vocational High Schools (Sekolah Menengah Kejuruan or SMK) possess a crucial role in preparing students to get involved in the workforce. Students are ready to  work if they have relevant work experience, master competency, and own strong soft skills. This readiness can be achieved when students actively participate in Internship Programs (Praktik Kerja Lapangan or PKL), hold competency certificates as proof of skill mastery, exhibit strong soft skills, and show a genuine interest in working. This study aims to examine the influence of internship experience, competency certification, and soft skills on students’ work readiness, with job interest acting as a moderating variable. A quantitative approach was employed by distributing questionnaires to 12th-grade students majoring in Accounting and Financial Institutions at private vocational schools in Tangerang City. The study involved 359 respondents from 25 schools, selected using a non-probability sampling technique. Data were analyzed using SmartPLS 4.0 software. The results indicate that internship experience, competency certification, and soft skills have a positive and significant effect on students' work readiness. Furthermore, job interest is proven to moderate the relationship between these variables and work readiness.